Development of a Medication Box with an Alert System Using 3D Printing Technology - ไอยราพัฒนา, เจษฎา; พิมพ์ศรี, เขมณัฏฐ์; ครุฑกล่อม, ชนะ; นาคสุข, พุทธินันท์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
The research titled Development of a Medication Box with Notification System Using 3D Printing Technology aims 1) to study the design and development of a medication box with a notification system using 3D printing technology, 2) to evaluate the efficiency of the design and development of the medication box using 3D printing technology, and 3) to assess the actual usage and user satisfaction with the medication box with a notification system developed using 3D printing technology. The population includes elderly individuals and the general public, with a sample group of 30 individuals who use medication in their daily lives, selected through purposive sampling. The research instruments consist of 1) the medication box with a notification system developed using 3D printing technology, 2) an efficiency evaluation form assessed by experts, and 3) a satisfaction questionnaire for the sample group.The development of the pillbox with an alert system using 3D printing technology was evaluated by three experts. The evaluation showed a high level of efficiency, with a mean score (X̅) of 3.53 and a standard deviation (S.D.) of 0.61. The most highly rated aspect was the accuracy of the alert system (sound and light).Furthermore, the user satisfaction evaluation of the design and development of the pillbox showed a high level of satisfaction, with a mean score (X̅) of 3.94 and a standard deviation (S.D.) of 0.72. The most highly rated aspect was the usefulness and ease of use of the alert system. Based on the research results, it can be concluded that the design and development of the pillbox with an alert system using 3D printing technology resulted in a device that performs effectively according to the set objectives. The pillbox is durable, cost-effective for reproduction, and the alert system can be programmed to remind users to take their medication accurately using sound or visual alerts. This helps reduce the issue of forgetting to take medication, achieving the intended purpose of the design.